SMART CONTRACT TECHNOLOGY FOR DIGITALIZATION AND AUTOMATION PROOF OF DELIVERY IN SUPPLY CHAIN MANAGEMENT - Iman Kusnadi; Catharina Badra Nawangpalupi; Carles` Sitompul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The Proof of Delivery (POD) document is essential for confirming the receipt of products and facilitating invoice generation in logistics operations. The persistent reliance on physical papers results in inefficiencies, including document loss, verification delays, and restricted visibility. This research introduces a blockchain technology-based smart contract POD system designed to enhance operational transparency, security, and efficiency. A case study at an Indonesian logistics company evaluates the transition from a manual to a digital Proof of Delivery (POD) process through prototype development and field trials. Essential findings indicate that blockchain facilitates unalterable, instantaneous documentation and verification, whereas smart contracts streamline multi-phase validation processes. The suggested approach decreases verification time from 20 days to mere minutes, mitigates human error, and enhances invoice precision. The prototype of a smart contract application suggests faster processing times and lower costs per transaction, among other benefits. Errors of inputs are also reduces, indicating a significant boost in data accuracy.